Photosensitized degradation of caffeine: Role of fulvic acids and nitrate - Jacobs, Laura E.; Weavers, Linda K.; Houtz, Erika F.; Chin, Yu-Ping (Chemosphere (Oxford), 2012)
► Caffeine photodegradation occurs slowly in water. ► Caffeine photodegradation is enhanced in the presence of fulvic acids. ► Caffeine indirect photolysis at 10 μM and higher reacts via the hydroxyl radical. ► Nitrate enhances caffeine’s hydroxyl radical pathway. ► Photolysis at low initial concentration caffeine ( <0.1 μM) occurs more quickly. The photolysis of caffeine was studied in solutions of fulvic acid isolated from Suwannee River, GA (SRFA) and Old Woman Creek Natural Estuarine Research Reserve, OH (OWCFA) with different chemical amendments (nitrate and iron). Caffeine degrades slowly by direct photolysis (>170 h in artificial sunlight), but we observed enhanced photodegradation in waters containing the fulvic acids. At higher initial concentrations (10 μM) the indirect photolysis of caffeine occurs predominantly through reaction with the hydroxyl radical (OH ) generated by irradiated fulvic acids. Both rate constant estimates based upon measured OH steady-state concentrations and quenching studies using isopropanol corroborate the importance of this pathway. Further, OH generated by irradiated nitrate at concentrations present in wastewater effluent plays an important role as a photosensitizer even in the presence of fulvic acids, while the photo-Fenton pathway does not at neutral or higher pH. At lower initial concentrations (0.1 μM) caffeine photolysis reactions proceed even more quickly in fulvic acid solutions and are influenced by both short- and long-lived reactive species. Studies conducted under suboxic conditions suggest that an oxygen dependent long-lived radical e.g., peroxyl radicals plays an important role in the degradation of caffeine at lower initial concentration.